Chapter 6 Differentiated alignment and Nordic cooperation in security and defence - Fedorchak, Viktoriya (Taylor & Francis, 2025)
This book analyses differentiation in European integration from a Nordic perspective. Following an interdisciplinary approach and focusing on the idea of the Nordics as a laboratory of differentiation, the book explores specific Nordic concerns in policy fields such as the labour market, security and Justice and Home Affairs (JHA), EU institutions such as the European Commission and the Eurogroup, and legal issues such as the European Economic Area (EEA) law and European patent law. It discusses differentiation, particularly from the Nordic experiences, examines the lessons that can be learnt from them, and suggests more 'hidden' and less researched cases. This book will be of key interest to scholars and students of European studies, European integration, Nordic studies, differentiated integration and more broadly to comparative politics.